Sleep Quality of SHS STEM Students Post-pandemic - Encabo, Justin Jacob; Berja, Hazel Marie; Chavez, Chrissa Leaj; Dela Pena, Sheila Mae; Dormindo, Juliana Marie; Lim, Jwennyth Wackyn; de Oca, Phillip Raymund (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Sleep is an integral component of maintaining overall health and well-being. Inadequate sleep can result in detrimental effects, both on mental and physiological aspects. While the impact of the COVID-19 pandemic on students' sleep quality was extensively examined, there remains a dearth of literature investigating the prevalence of sleep quality after the shift to a post-pandemic lifestyle. This study utilized a descriptive design and gathered data from 202 randomly selected grades 11 and 12 STEM students. We found that 68.81% of them have poor sleep quality. Data also showed that female students obtained high PSQI scores and had a significantly higher prevalence of poor sleep quality than males. However, there was no significant difference in sleep quality between grade levels. In conclusion, sleep quality among STEM students in the post-pandemic setting is poor, implying the need for further assessment of influencing factors in students' sleep patterns, strategies, and management skills. Furthermore, students should be educated on the importance of sleep and the negative consequences of poor sleep quality on regular activities, mental & physical health, and general well-being.